Molecular identification and prevalence of fungal contaminants in seeds of semi-annual crops - Patiño-Moscoso, Manuel Alfonso (2023)
Seed quality is affected by fungal contamination. These cause abortion, rot, or necrosis of the seed, as well as seedling damage that results in the development of diseases in later stages of growth. Their identification and characterization are essential to establish appropriate management. The objective of this work was to identify and determine the prevalence of fungal contaminants present in the seed of thirteen plant varieties of rice, soybean, corn, and forage sweet sorghum produced in the municipality of El Espinal, Tolima, Colombia. This research was carried out at the Tibaitatá Research Center of the Colombian Agricultural Research Corporation AGROSAVIA (Cundinamarca, Colombia) during the second semester of 2021. By means of a blotter test, fungal contaminants and their prevalence in germinated and non-germinated seeds were identified. A total of 65 fungal isolates were obtained, which were grouped into twenty-eight molecularly identified morphotypes (44 soybean, 5 rice, 7 sorghum and 9 corn). The genera Diaporthe and Fusarium were the ones with the highest total prevalence and in ungerminated seeds. The fungi found include possible pathogens such as Fusarium spp, Curvularia spp and Diaporthe spp. and saprophytic fungi such as Penicillium spp and Aspergillus spp. The isolates of Fusarium equiseti and Diaporthe sp. in soybean seed, Curvularia penniseti in rice seed, Diaporthe melonis in sorghum seed and Fusarium verticillioides in corn seed can be considered as potential seed-borne pathogens that caused a negative effect on germination capacity.